2016
DOI: 10.3389/fmicb.2016.00774
|View full text |Cite
|
Sign up to set email alerts
|

Stable Isotope Phenotyping via Cluster Analysis of NanoSIMS Data As a Method for Characterizing Distinct Microbial Ecophysiologies and Sulfur-Cycling in the Environment

Abstract: Stable isotope probing (SIP) is a valuable tool for gaining insights into ecophysiology and biogeochemical cycling of environmental microbial communities by tracking isotopically labeled compounds into cellular macromolecules as well as into byproducts of respiration. SIP, in conjunction with nanoscale secondary ion mass spectrometry (NanoSIMS), allows for the visualization of isotope incorporation at the single cell level. In this manner, both active cells within a diverse population as well as heterogeneity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…Remarkably, there were also dozens of novel phylotypes affiliated with the Thiotrichales detected using 16S rRNA as well as aprA gene sequencing. Other studies of shallow vents have found members of the Thiotrichales to be key members of the chemoautotrophic vent communities ( Brinkhoff et al, 1999 ; Dawson et al, 2016 ). However, a number of studies in both shallow and deep-sea vents systems have found mesophilic Epsilonproteobacteria such as Sulfurovum and Sulfurimonas to be the most common groups of SOxB recovered by molecular means ( Flores et al, 2012 ; Sylvan et al, 2012 ; Wang et al, 2015 ) and cultivation ( Inagaki et al, 2003 , 2004 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Remarkably, there were also dozens of novel phylotypes affiliated with the Thiotrichales detected using 16S rRNA as well as aprA gene sequencing. Other studies of shallow vents have found members of the Thiotrichales to be key members of the chemoautotrophic vent communities ( Brinkhoff et al, 1999 ; Dawson et al, 2016 ). However, a number of studies in both shallow and deep-sea vents systems have found mesophilic Epsilonproteobacteria such as Sulfurovum and Sulfurimonas to be the most common groups of SOxB recovered by molecular means ( Flores et al, 2012 ; Sylvan et al, 2012 ; Wang et al, 2015 ) and cultivation ( Inagaki et al, 2003 , 2004 ).…”
Section: Discussionmentioning
confidence: 97%
“…This raises the possibility of a complete biological sulfur cycle mediated by partnerships between oxidative and reductive sulfur bacteria. Tightly coupled (cryptic) sulfur cycling, where physically associated oxidative and reductive metabolic types co-exist, has been identified in phototrophic microbial mats and consortia ( Fike et al, 2008 ; Wilbanks et al, 2014 ), and has recently been demonstrated in a companion investigation to this one ( Dawson et al, 2016 ) in the White Point (WP) chemosynthetic vent mat communities found in the Palos Verdes (PV) hydrothermal vent field in San Pedro, CA, USA. However, it is not clear how significant a role biological sulfur/sulfate reduction plays in the WP mats.…”
Section: Introductionmentioning
confidence: 99%
“…(e.g., Kopf et al, 2015;Dawson et al, 2016;Wegener et al, 2016). Despite the frequent application of multi-isotope nanoSIP in relatively low-throughput analyses targeting particular taxa (e.g., dozens of FISH-identified cells), it has rarely been used as a high-throughput metabolic screening technique to characterize hundreds to thousands of individual, unidentified cells (Dawson et al, 2016;Arandia-Gorostidi et al, 2017). Used in this manner, it has the potential to analyze enough cells to generate metabolic activity profiles representative of the entire community.…”
Section: Discussionmentioning
confidence: 99%
“…These questions require culture independent, quantitative, singlecell approaches. Techniques to accomplish this exist, such as nanoSIP (Pett-Ridge and Weber, 2012) and microautoradiography (Okabe et al, 2004), and illustrate within-population variation in metabolism and growth (e.g., Popa et al, 2007;Finzi-Hart et al, 2009;Kopf et al, 2015;Zimmermann et al, 2015;Dawson et al, 2016;Dekas et al, 2016). However, these studies are often limited in scope due to their low-throughput, typically analyzing a few to dozens of cells per analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Nano-scale secondary ion mass spectrometry (NanoSIMS) has also been used to detect the uptake of labeled substrates as an indicator of metabolic activity, allowing for single-cell resolution, which can be useful for describing rare members of the community [ 156 , 157 ]. In combination, NanoSIMS and FISH can be used to link metabolism to phylogeny, allowing for the identification of active members of a microbial community [ 158 , 159 ].…”
Section: Viability Assays Based On Cellular Metabolism and Other Propmentioning
confidence: 99%